The realities of participation in planning in Bangladesh : the role of institutional and socio-political factors in shaping participatory planning in developing countries - Swapan, Mohammad Shahidul Hasan (Curtin University, 2013)
Despite similar rhetoric and stated policies, there are major differences found in planning and management of cities in developed and developing countries. These differences are most evident in the degree of involvement of citizens in planning and urban governance processes. Democratic traditions prevalent in these countries stemming from historical factors and the evolutionary paths of urbanization followed and the resulting socio-economic and cultural condition could partially explain these differences.Multifaceted challenges and unpredictable political environment in developing countries, however, complicate the nature of governance and community participation to the extent that theoretical models explaining community participation found in the literature do not adequately reflect the widespread realities of developing countries. The gap between planning theory mainly evolved in the developed western nations’ context and development practices in the developing countries thus warrants a comprehensive investigation from an interdisciplinary outlook.Over many decades, the discourse of planning and development theory and practice in developing countries has been largely prescribed by international aid agencies. This may be seen as transplanting theoretical concepts evolved in the developed western countries with inadequate regard to local conditions and realities. As such the prescriptions for community participation focus largely on reform of institutional factors while largely ignoring socio-political factors that also affect individual’s propensity to participate in planning processes.Relying on an empirical study carried out for this dissertation on citizens’ experience regarding participation in urban planning in Dhaka, Bangladesh, this study focuses on the dynamics of citizens’ participation. It seeks to develop a community participation model that reflects the realities of citizens in developing countries. Taking an interdisciplinary perspective, it attempts to map out the major dimensions that characterise the complex phenomenon of participation.Empirical evidence suggests that participation is low due to a range of internal and external factors. Lack of public awareness, trust in planning agencies and a sense of urgency were identified as prime internal factors negatively affecting citizens’ participation. The study also points to the existence of high levels of social networking and an established client and patron system operating parallel to and outside the formal urban planning framework that tends to undermine community participation in urban planning processes.The study concludes by proposing a community participation model that is not concerned solely with transferring power from government to citizens, but also takes into account participants’ realities that shape the attitude and tendency of citizens towards participation. It is found that citizens’ decision to participate in planning processes depends on the interactions between citizens and government, prevalent socio-political context and external forces. Citizens tend to avoid engaging in formal participation processes where there is an option to engage in a parallel system of informal transactions that they perceive to be more effective than formal planning system.The community participation model developed through the study of the Bangladesh context could be used to redefine the role of institutions and concerned authorities to inspire genuine participation that could lead to sustainable urban development outcomes.